The Effect of Leadership Styles on Organizational Performance in Public Sector Organizations in Nepal - Chand, Umesh (The Management Review, 2026)
Leadership plays a significant role in enhancing organizational performance in private and public sector organizations. This research aims to investigate the impact of transformational, transactional, autocratic, and democratic leadership on organizational performance of Nepalese public sector organizations. This research is based on quantitative research, and the research design is cross-sectional. The research collected data from 350 employees of public sector organizations, including universities, hospitals, and local governments of Nepal, using a structured questionnaire. The research used descriptive statistics, reliability, correlation, and regression analyses to analyze the collected data. The findings of the research indicate that transformational and democratic leadership have a high positive impact on organizational performance. Transformational leadership is more significant, whereas transactional leadership is significant but to a lower extent. The findings of the research indicate that autocratic leadership is negatively correlated with organizational performance. This research contributes to the body of knowledge on leadership and public administration by adding empirical findings on the ailing Nepalese public sector and by using one umbrella to analyze various leadership styles. The findings of the research will be helpful for policymakers and executives of public sector organizations to promote democratic and transformational leadership for enhancing organizational performance.